Microplastic ingestion by commercial marine fish from the seawater of Northwest Peninsular Malaysia - Yuen Hwei Foo; Sharnietha Ratnam; Er Vin Lim; Masthurah Abdullah; Vincent J. Molenaar; Aileen Tan Shau Hwai; Shoufeng Zhang; Hongjun Li; Norlaila Binti Mohd Zanuri (PeerJ, 2022)
Over the past decade, concerns over microplastic pollution in the marine ecosystem has increasingly gained more attention, but research investigating the ingestion of microplastics by marine fish in Malaysia is still regrettably lacking. This study investigated the microplastic presence, abundance, and morphological types within the guts of four species of commercial marine fish (Atule mate, Crenimugil seheli, Sardinella fimbriata and Rastrelliger brachysoma) caught in seawater off the coast of Malaysia’s Northwest Peninsular. A total of 72 individual commercial marine fish guts from four species (fish per species n = 18) were examined. Remarkably, this study found that 100% of the samples contained microplastics. A total number of 432 microplastics (size < 5 mm) from the four species were found in the excised marine fish guts. The most common type of microplastic discovered was fragment, which accounted for 49.5% of all microplastics present. The gut microplastic content differed between species. Sardinella fimbriata recorded the greatest amount of microplastic ingestion, with an average microplastic count of 6.5 (±4.3) items per individual fish. However, there were no statistically significant differences found when comparing study species and different locations. SEM-EDX analysis confirmed the presence of microplastic particles by identifying the chemical elements found in the samples. Since the four studied species of commercial marine fish are popular protein sources in Malaysians’ daily diet, this study suggests potential microplastic exposure to humans via contaminated fish consumption in Malaysia, which was previously unknown. Based on previous scientific evidence, this study also demonstrates the high probability of microplastic ingestion in marine fish in the Malaysian seawater, which could have an adverse effect on fish health as well as marine biota.